Rapid Access to Functionalized γ-Lactams through Copper-Catalyzed Oxidative Cyclization of Diynes - Zhang, Ting-Ting; Wei, Kua-Fei; Ru, Guang-Xin; Zhu, Xiu-Hong; Xie, Li-Xia; Shen, Wen-Bo (Synlett, 2022)
An efficient copper-catalyzed oxidative cyclization of diynes is described. A range of functionalized γ-lactams can be readily constructed by using this protocol. This copper-catalyzed oxidative process proceeds through an alkyne oxidation, carbene/alkyne metathesis, and donor–donor carbene oxidation sequence. The use of readily available substrates, high flexibility, a simple procedure, and mild reaction conditions render the procedure a viable alternative for the preparation of functionalized γ-lactams.
Keywords: copper catalysis; diynes; oxidation; carbene/alkyne metathesis; γ-lactams